Shodaqoh Infaq Management Model to Increase Community Economic Welfare - Kurjono Kurjono; J. Juliana; Tatang Hidayat (Perhimpunan Intelektual Muslim Indonesia, 2023)
The purpose of the study is to analyze how empowering the infaq shodaqoh fund managed by the Mosque can have more added value to improve the welfare of the surrounding community. The research method used is qualitative with a Research and development approach. The results showed that the mosque not only functions as a place of worship but has a more special social and economic function in terms of empowerment. The infak shodaqoh fund, if appropriately managed and professionally, can improve the community's welfare. This is done by carrying out an empowerment model by the DKM management to be used as a revolving fund. Furthermore, this study implies that the infaq shodaqoh fund can improve people's welfare from an economic aspect. This is done by conducting an economic empowerment model.